Três ensaios em demografia de empresas - (:unkn) unknown (Outro, 2018)
This study investigates the demographics of companies at Rio Grande do Sul State from 2006 to 2013. First, the birth, mortality and turnover of companies are quantified, as well as their survival over time. Then, these demographic events are analyzed by size, economic activity, and geographic location. For this purpose, an identified database is used, which allows the longitudinal monitoring of all formal companies existing in Rio Grande do Sul over the period under study.
Three essays on company demographics
Keywords: Demografia de empresas; Sobrevivência de empresas; Rotatividade de empresas; Demographics of companies; Survival of companies; Turnover of companies; CNPQ::CIENCIAS SOCIAIS APLICADAS